ROUTING MANAGEMENT OF EXPERIENCE TOURISM IN COASTAL EASTERN REGION, THAILAND - นาคปฐม, ปริญญา; พลีรักษ์, ณรงค์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The objectives of research aim to 1) study the experience tourism destinations 2) present activities in experience tourism destinations and 3) develop the route of experience tourism in the eastern coastal region of Thailand. The result is explored and summarized by qualitative research techniques: documentary analysis, in-depth interview, non-participant observation, and survey in the prospective experience tourism destinations. The potential experience tourism destinations are in 4 provinces; Chonburi, Rayong, Chantaburi, and Trat. The key informants consist of a leader in tourism destinations, tourists, and local people who are in 32 prospective experience tourism destinations. The research instruments are interview form and possibility assessment in being an experience tourism destination. The result of the research shows 32 tourism destinations which are located in the eastern coastal region, Thailand. They are classified into 3 groups; there are 21 tourism destinations in the high potential to be experience tourism destinations, there are 9 tourism destinations in the moderate potential to be experience tourism destinations, and there are 2 tourism destinations in the low potential to be experience tourism destinations. Moreover, experience tourism destinations in group 1 are managed into 3 routing pattern which are 9 routes for a one-day trip, 5 routes for 2 days 1 night and 4 routes for 3 days 2 nights.